2019
DOI: 10.1371/journal.pone.0225877
|View full text |Cite
|
Sign up to set email alerts
|

Expanded eligibility for HIV testing increases HIV diagnoses—A cross-sectional study in seven health facilities in western Kenya

Abstract: Homa Bay, Siaya, and Kisumu counties in western Kenya have the highest estimated HIV prevalence (16.3–21.0%) in the country, and struggle to meet program targets for HIV testing services (HTS). The Kenya Ministry of Health (MOH) recommends annual HIV testing for the general population. We assessed the degree to which reducing the interval for retesting to less than 12 months increased diagnosis of HIV in outpatient departments (OPD) in western Kenya. We conducted a retrospective analysis of routinely collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…Although we did not assess socioeconomic status directly, we found manual/domestic or trade/sales/service occupations were associated with higher risk of HIV infection, which might be explained by an unidentified interplay between source of income and behavior, including increased opportunity for social interaction and travel. Our findings are also consistent with program data from western Kenya which found that patients who had never been tested for HIV, or had a negative HIV test result > 12 months prior were more likely HIV-positive [76]. Most patients (95%) had been tested for HIV within the previous 12 months, reflecting intensified HIV testing efforts to increase ART coverage in the study region [77][78][79][80].…”
Section: Discussionsupporting
confidence: 88%
“…Although we did not assess socioeconomic status directly, we found manual/domestic or trade/sales/service occupations were associated with higher risk of HIV infection, which might be explained by an unidentified interplay between source of income and behavior, including increased opportunity for social interaction and travel. Our findings are also consistent with program data from western Kenya which found that patients who had never been tested for HIV, or had a negative HIV test result > 12 months prior were more likely HIV-positive [76]. Most patients (95%) had been tested for HIV within the previous 12 months, reflecting intensified HIV testing efforts to increase ART coverage in the study region [77][78][79][80].…”
Section: Discussionsupporting
confidence: 88%
“…Although several studies have documented a correlation between widowhood and higher HIV infection [ 44 , 45 , 50 ], a significant association between widowed individuals and HIV-positive diagnosis was not observed in this study. Similar to findings observed in facility-based testing [ 51 ], individuals never tested for HIV, and those tested > 12 months prior, were more likely to be diagnosed HIV-positive. The association between increasing age and higher likelihood of HIV diagnosis found in this study is consistent with higher HIV prevalence observed in older age groups [ 52 – 54 ].…”
Section: Discussionsupporting
confidence: 76%
“…One study further suggests routine HIV testing for not only patients but also those who accompany patients to the health care facilities in the communities of high HIV prevalence. [41] In general, our findings suggest that routine HIV screening in dental setting is beneficial where routine HIV screening in primary care setting is mandated, because our data show that a large percent of dental patients have never been tested for HIV, have not seen a primary care provider or have not been offered an HIV screening test by a primary care provider in the past year.…”
Section: Plos Onementioning
confidence: 65%